Get a Room! How Writing Groups Aid the Development of Junior Academics’ Writing Practice and Writer Identity - Mattsson, Jenny; Brandin, Emma-Karin; Hult, Ann-Kristin (Journal of Academic Writing, 2020)
The present study revisits writing retreat participants who have spontaneously formed writing groups before or after attending a retreat hosted by the Unit for Academic Language at the University of Gothenburg, Sweden. All in all, 11 doctoral students and one postdoc were interviewed using a semi-structured interview model. The answers were thematically analysed based on Murray’s (2014) concept of coherence in writing groups as well as parts of Aitchison and Lee’s (2006) key characteristics of writing groups. The two main research questions posed concern (i) whether the informants have changed their writing practice and/or the way they think and feel about writing since joining a writing group, and (ii) whether possible changes have aided the development of their identity as academic writers. Results show that the informants have indeed changed central aspects of their writing practice and that this in turn has positively influenced how they now think and feel about writing. This has to some extent contributed to the informants’ development of their writer identity; however, the present study also sheds light on the fact that more needs to be done at departmental levels across the university to make academic writing visible.